Enhancing Student Engagement and Experience through Technology-Based Collaborative Learning in Language Education - Muhmmad Nur Ashari; Ventje Jany Kalukar; Ichi Ahada; Bibit Suhatmady (Universitas Islam Negeri Palopo, 2026)
This study addresses the limited exploration of students’ perspectives on technology-enhanced collaborative learning in English language education, particularly in Indonesia as a developing country context. The study aims to investigate how technology-mediated collaboration enhances student engagement and learning experiences. Guided by the Technological Pedagogical Content Knowledge (TPACK) framework and Vygotsky’s social constructivism, this qualitative research involved five students from the English Department of Mulawarman University who actively participated in digital collaborative projects. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings reveal that technology enhances student engagement by promoting active participation, flexibility, and collaborative interaction. Digital tools such as Google Docs, Canva, Zoom, and WhatsApp supported clearer role distribution, improved communication, and facilitated better understanding of English through accessible learning resources. Students also reported increased motivation, confidence, and responsibility in group work. However, several challenges were identified, including unstable internet connections, unequal participation, and occasional miscommunication. Overall, technology-assisted collaborative learning fosters meaningful learning experiences while supporting students’ language and communication development.